Business Opportunities For Trading Traditional Gold Mining Equipment In Lebong Tambang Village, Lebong Regency - Reni Doyun Putri; Putra Pernales; Ahmad Soleh; Muhammad Rahman Febliansa (Universitas Dehasen Bengkulu, 2026)
Traditional gold mining in Lebong Tambang Village, Lebong Regency, has long been a major source of community income and has driven the growth of MSMEs in artisanal mining equipment trade. This study analyzes the key determinants of business success and formulates sustainable development strategies for artisanal mining areas. Using a descriptive qualitative approach through literature review and document analysis of government reports and scientific publications, the study examines market opportunities, business challenges, and relevant strategies for mining equipment MSMEs. The findings identify four main success factors: partnerships with local miners, improved product quality and after-sales service, digital marketing utilization, and the application of safety and environmental principles in equipment production. Despite strong development potential, MSMEs face challenges including limited capital, legal constraints related to artisanal mining, and occupational safety risks. Overall, the mining equipment trade in Lebong Regency has significant growth prospects if supported by collaboration, product innovation, and supportive regulations and financing, contributing to sustainable local economic development and improved community welfare.